2015
DOI: 10.1016/j.yhbeh.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors in the central nervous system and their implication for dopamine-dependent cognition in females

Abstract: Over the past 30 years, research has demonstrated that estrogens are not only important for female reproduction, but play a role in a diverse array of cognitive functions. Originally, estrogens were thought to have only one receptor, localized exclusively to the cytoplasm and nucleus of cells. However, it is now known that there are at least three estrogen receptors (ERs): ERα, ERβ and G-protein coupled ER1 (GPER1). In addition to being localized to nuclei, ERα and ERβ are localized to the cell membrane, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
181
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(187 citation statements)
references
References 179 publications
(283 reference statements)
5
181
0
1
Order By: Relevance
“…GPER1, the membrane E-receptor, has been found throughout the rodent brain with high levels in the olfactory bulbs, hypothalamus, LC, the hippocampus, the habenular nucleus of the epithalamus, nucleus of the solitary tract, cortical regions including the motor, somatosensory piriform cortices, as well as the Purkinje and granule cells of the cerebellum (Almey et al, 2015). While many functions of GPER1 have been described, information on the hormonal regulation of GPER1 is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPER1, the membrane E-receptor, has been found throughout the rodent brain with high levels in the olfactory bulbs, hypothalamus, LC, the hippocampus, the habenular nucleus of the epithalamus, nucleus of the solitary tract, cortical regions including the motor, somatosensory piriform cortices, as well as the Purkinje and granule cells of the cerebellum (Almey et al, 2015). While many functions of GPER1 have been described, information on the hormonal regulation of GPER1 is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these rapid actions may initiate and support longer term actions on gene expression (Levin, 2015). For example, the estrogen specific membrane protein, GPER1, is ubiquitously expressed and found in many areas of the brain (Almey et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the localisation of GPER1 in rodent brain and have reported high levels of GPER1 expression in both cortical and hippocampal regions (Brailoiu et al, 2007;Hazell et al, 2009;Almey et al, 2014;Almey et al, 2015). Expression of GPER1 has also been detected in the basal forebrain, thalamus and dorsal striatum (Brailoiu et al, 2007;Hazell et al, 2009).…”
Section: Gper1 Expression In the Brainmentioning
confidence: 99%
“…The effect on dopamine systems could underlie some of the sex differences in motivated behavior (Yoest et al, 2014). Estrogen receptor subtypes α and β as well as GPER1 are located in both nuclei and membranes in dopaminergic areas (Almey et al, 2015). While concentrations of ERα are low in dopamine neurons, ERβ is relatively abundant in dopamine cell bodies in the substantia and ventral tegmental area in both male and female rats (Creutz and Kritzer, 2002).…”
Section: Neurological Effects Of Estrogenmentioning
confidence: 99%